INDONESIAN LANGUAGE EDUCATION BASED ON LEARNING OUTCOMES IN THE TEACHING MATERIALS DEVELOPMENT COURSE AT THE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Rita Rita; Ali Ali; Ratna Soraya; Rika Kartika (SOSIOEDUKASI, 2026)
This study aims to describe Indonesian language education based on learning outcomes in the Teaching Material Development course at the Islamic University of North Sumatra. This study uses a qualitative approach with a descriptive type of research. Data was collected through in-depth interviews, learning observations, and documentation studies, then analyzed using an interactive analysis model. The results of the study show that the formulation of learning outcomes has referred to the learning outcomes of graduates, but some of the formulations are still general and have not been fully measured. The implementation of learning has implemented an active learning strategy, but the relationship between learning activities and learning outcomes has not been fully understood by students. The development of Indonesian teaching materials shows a systematic structure, but learning evaluation is still predominantly oriented towards the knowledge aspect. This study concludes that it is necessary to strengthen the alignment between learning outcomes, learning strategies, and evaluation systems to improve the quality of Indonesian learning in higher education.